Collusion, Blackmail and Whistle-Blowing - Leonardo Felli; Rafael Hortala-Vallve (Center for Economic Studies and ifo Institute (CESifo), 2015)
Whistle-blowing is usually regarded as a way to identify abuse and wrongdoing on the part of governments and corporations. In this paper we show how, at a micro level, whistle-blowing can be used as a designer tool to prevent opportunistic behavior, that takes the form of collusion or blackmail, on the part of members of a simple hierarchical structure. We focus on a three layered principal-supervisor-agent structure and show how the principal can use whistle-blowing as a way to prevent the supervisor and the agent from colluding to the detriment of the principal. To understand our mechanism we need to explicitly define the penalty a party has to incur for walking away from a collusive agreement. Rewarding whistle-blowing, creates incentives for the uninformed colluding party to walk out of the side deal and report to the principal that collusion took place. This threat clearly reduces the informed party's incentive to participate in side deals. It also serves as a potential blackmail threat between the colluding parties. However, careful use of whistle-blowing allows the principal to eliminate opportunities for blackmail.
Keywords: D73; D78; D83; 330; collusion; blackmail; whistle-blowing and communication